Parathyroid Hormone Related Protein - A Skeletal Biomarker – A Review - A. Arif Yezdani, (Institute of Medico-legal Publications Pvt Ltd, 2020)
The discovery of Parathyroid hormone-related protein (PTHrP) was through its structural and functionalhomology with parathyroid hormone. It is secreted by cancers and it interacts with parathyroid hormonereceptors in kidney and bone to cause humoral hypercalcemia of malignancy and paraneoplastic syndrome andplays an important role in cellular differentiation and proliferation, embryonic development, transepithelialcalcium transport and in the regulation of smooth muscle contraction.Its intracrine, paracrine and endocrinemodes of action play a central role in organogenesis and drives numerous physiologic and pathologicconditions.It is initially translated as a preprohormone which is posttranslationally processed to yield afamily of mature secretory forms. The aminoterminal portion of the molecule is homologous to parathyroidhormone.As PTHrP plays a vital role in the regulation of endochondral bone development it was surmisedthat it could also serve as an ideal biologic skeletal maturity indicator to detect peak pubertal growth spurt.